Assessment of removal efficiency of pharmaceutical products from wastewater in sewage treatment plants: A case of the sewerage systems Ghana limited, Accra - Kwadwo Kodom (Elsevier, 2021)
Pharmaceuticals put the environment at high risk when found in products of wastewater treatment plants, hence need to be removed efficiently. This study quantified selected pharmaceutically active compounds (PhACs) (diclofenac, aspirin, paracetamol, and ibuprofen) in wastewater and evaluated its removal efficiency from wastewater treatment plant (WWTP). Samples were taken from the WWTP of the Sewerage Systems Ghana Limited (SSGL) for 18 consecutive days. Both effluents and influents were tested in the laboratory to determine the concentrations of the various pharmaceutical products. The results reveal diclofenac as the PhAC with the highest concentration in the influent with an average of 121.31 μg/ml. Paracetamol recorded an average of 65.54 μg/ml, then ibuprofen with an average of 19.54 μg/ml. Aspirin was the PhAC with the lowest concentration in the influent with an average of 0.27 μg/ml. Further assessment was also done on the trickling filter (biological filter) which is part of the process plant at the secondary stage to assess how the trickling filter aids in the removal of these selected pharmaceuticals.The average removal efficiency found were; diclofenac 74%, aspirin 93%, paracetamol 98%, and ibuprofen 99%. The technologies suggested for improvement, particularly for diclofenac, based on comprehensive literature were phototransformation and sorption of diclofenac onto sludge which occurs via absorption and adsorption, that can be adopted by the management of the WWTP at SSGL to help increase the removal efficiency of the selected PhACs. It was also identified that the trickling filter is the stage that substantially aids in the removal of the selected pharmaceuticals due to its special features.